Effect of six weeks of blood flow restriction combined with Tabata training on anaerobic capacity in male badminton players - Xia, Yuancheng; Zheng, Xin; Zhou, Kaixiang; Jiang, Leyi; Song, Bojun; Xu, Shuxian; Shang, Zhangyuting; Dai, Jin (Frontiers in Physiology, 2025)
BackgroundBlood flow restriction (BFR) combined with high-intensity interval training (HIIT) is increasingly recognized as an effective strategy for enhancing aerobic capacity and muscle strength in athletes. However, there is no consensus on the effects of BFR combined with HIIT on anaerobic capacity.ObjectiveThis study aims to examine the effects of BFR combined with Tabata training (BFR-Tabata), a type of HIIT, on anaerobic capacity in male badminton players.MethodsThirty male badminton players (age: 20.4 ± 1.2 years) were randomized to the BFR-Tabata group (n = 15) or the Tabata group (n = 15). Both groups performed 6 weeks (3 times per week) of Tabata training (20 s maximal effort/10 s rest x 8 sets x 4 rounds). Pre and post-intervention assessments included a 30-s Badminton-specific endurance test, countermovement jump (CMJ), squat jump (SJ), and Wingate anaerobic test (peak power [PP], average power [AP], fatigue index [FI], time to peak [TTP]). A two-way repeated measures ANOVA (time × group) was used to analyze training effects, with Bonferroni post hoc tests. Effect sizes were reported as partial eta squared (ηp2) or Cohen’s d, with significance set at p < 0.05.ResultsThe BFR-Tabata training intervention significantly improved anaerobic endurance among male badminton athletes. In comparison to the Tabata group, the BFR-Tabata group exhibited statistically significant differences in badminton-specific endurance (p = 0.02, d = 0.92, moderate effect) and multiple anaerobic performance indicators assessed by the Wingate test, including PP (p = 0.01, d = 1.11, moderate effect), AP (p < 0.01, d = 1.51, large effect), and TTP (p < 0.01, d = 2.10, very large). However, no statistically significant difference was observed in lower limb explosive strength measures, including CMJ (p = 0.50, d = 0.25, small effect), SJ (p = 0.56, d = 0.21, small effect), or during the Wingate test the FI (F = 0.138, p = 0.71, ηp2 = 0.005, trivial effect).ConclusionBlood flow restriction combined with Tabata training is an effective strategy for improving anaerobic capacity in male badminton players, but it has limited enhancement of lower-limb explosive strength.